Decolonization and Reconciliation Work in Public Libraries: An Analysis of Strategic Plans - Rathi, Dinesh (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2021)
<span data-sheets-value=""1":2,"2":"The 2015 Truth and Reconciliation Commission of Canada report provides valuable guidance and critical foundation on decolonization and reconciliation in Canada. Public institutions including universities and libraries have affirmed their commitment towards reconciliation and decolonization by undertaking initiatives and establishing both short- and long-term goals. This research examines strategic plans posted on the organizational websites of nine Canadian public library systems operating in cities with significant Indigenous population. The findings suggest that different library systems made varying levels of explicit and/or implicit commitment towards reconciliation and decolonization."" data-sheets-userformat=""2":8961,"3":"1":0,"11":0,"12":0,"16":12">The 2015 Truth and Reconciliation Commission of Canada report provides valuable guidance and critical foundation on decolonization and reconciliation in Canada. Public institutions including universities and libraries have affirmed their commitment towards reconciliation and decolonization by undertaking initiatives and establishing both short- and long-term goals. This research examines strategic plans posted on the organizational websites of nine Canadian public library systems operating in cities with significant Indigenous population. The findings suggest that different library systems made varying levels of explicit and/or implicit commitment towards reconciliation and decolonization.